TOPICAL ISSUES OF THE DEVELOPMENT OF SCIENTIFIC AND EDUCATIONAL ACTIVITIES IN THE HIGHER EDUCATION SYSTEM OF THE NORTH CAUCASUS FEDERAL DISTRICT (PART 1) - A. Borisenko (Вестник Северо-Кавказского федерального университета)
The article presents the results of the analysis of the main directions of development of scientific and educational activities in the universities of the North Caucasus Federal District, taking into account the goals and objectives of the digital transformation of the branch of science and higher education. It is shown that in order to increase the competitiveness of the regional higher education system, an interdisciplinary approach with mass personalization of the educational process and full-scale development of digital technologies should replace the subject-branch training of specialists. As a mechanism for launching such a system, it is proposed to consider the creation and centralized coordination of powerful creative teams by industry, the so-called «digital shockfists» or «digital special forces», including professionals from different fields of activity and, above all, an information technology specialist. Using the example of one of the industry directions «university -food production)}, the main goals of this direction of digital transformation are considered, as well as the reserve and tools available in NCFU to achieve it.